Relationship between neutrophil/lymphocyte ratio and left ventricular hypertrophy in maintenance hemodialysis patients - LI Lei; CAO Fang; LENG Yan-fei (Linchuang shenzangbing zazhi)
Objective To detect the neutrophil/lymphocyte ratio levels in maintenance hemodialysis(MHD)patients,and investigate their relationship with left ventricular hypertrophy(LVH).Methods A total of 96 patients undergoing MHD in Department of Nephrology of the First Hospital of Liangshan Prefecture from January 2018 to August 2019 were selected and divided into the high NLR group(NLR>3.31,n=47)and the low NLR group(NLR≤3.31,n=49).Baseline data,echocardiographic indexes [left atrial end-diastolic diameter(LAEDd),left ventricular end-systolic diameter(LVEDs),ejection fraction(EF),left ventricular mass index(LVMI)],laboratory indexes [NLR,brain natriuretic peptide(BNP),hemoglobin(HB),albumin(Alb),calcium)],blood lipid levels were compared to calculate the LVH incidence.All the patients were divided into LVH group and non LVH group according to whether LVH occurred or not.The high risk factors of LVH were analyzed by multivariate analysis,and the predictive value of NLR to LVH was analyzed by ROC curve.Results NLR was positively correlated with SBP,LAEDd,LVEDs,LVMI,NLR,BNP,Alb,LDL-C,Cholesterol,non-HDL-C,and Cr(P<0.05),and negatively correlated with DBP(P<0.05).The color Doppler ultrasonography indicated that the incidence of LVH in the high NLR group was higher than that in the low NLR group.Age,SBP,LAEDd,LVEDs,LVMI,NLR,BNP,Alb,LDL-C,TC,non-HDL-C,Cr were risk factors for LVH(P<0.05).The relative oddratio(OR)of NLR was the largest.NLR was a predictor of LVH(P<0.05).Conclusions NLR value is closely related to the occurrence and progression of LVH in MHD patients,so the monitoring of the NLR changes has significant value in the prevention and treatment of LVH.